Follow-up of HIV Positive Women Who had Abnormal Pap Smear Screening Results at Sanpatong Hospital, Chiang Mai Province, Thailand - Chaimani, Chutima; Torugsa, Somchart; Klinbuayaem, Virat; Promchan, Borpitt (Journal of Health Science of Thailand, 2017)
HIV-reactive women have increased risk of squamous intraepithelial lesion; nevertheless cervical cancer screening and treatment with effective follow up can reduce invasive risk. The objectives of this study were to assess the outcomes of cervical cancer screening and follow-up the treatment outcome among HIV-positive women attending Sampatong Hospital during January 2004 and December 2012. There were altogether 382 women with HIV who were screened with Pap smear during the study period (with a total of 1,720 visits); and 107 of them had abnormal screening results: 18 with ASC, 2 with AGC, 53 with LSIL, 33 with HSIL, and 1 with suspicious cancer. Tissue diagnoses were conducted, and the results revealed that 20 were normal, 43 were with LSIL, 39 with HSIL, and 5 with invasive cancer. Follow up within 1-year revealed that there were 22 women (21.57%) with abnormal screenings and the tissue diagnosis came out as 14 with LSIL, 6 with HSIL, and 2 had cervical cancer. For those 90 women who were followed up to 1-year or more, 5 died, and 20 (23.53%) with relapsed lesion (6 with LSIL and 14 with HSIL). Among 42 women with persisted lesions, 12 had had normal colposcopic studies. The relapse after treatment implied that there was a need for annual cervical cancer screening and continuous follow up for HIV-positive women.